Innovative approach: utilizing silver nanoparticles sheet for improved rabbit cecal anastomosis healing - Almohamad, Zakriya; Fahmy, Reham; Farag, Amany; Abdellatif, Ahmed; Mossallem, Wael; Abdallah, Abdelnaser A.; Abass, Marwa (Frontiers in Veterinary Science, 2024)
Introduction Anastomotic leakage is a severe complication associated with gastrointestinal surgery. The process of intestinal wound healing is crucial for the successful outcome of digestive tract surgical repair procedures. This research aimed to determine the impact of silver nanoparticles sheet (Acticoat) on the anastomotic healing of the cecum in rabbits. Methods A total of 48 New Zealand male rabbits in good health were used for cecum transection and anastomosis. The animals were randomized into the control group (C) and the silver nanoparticles group (AgNPs). In the C group, the transected cecum was end-to-end anastomosed with a single layer of simple continuous suture pattern using 3–0 polyglyconate. In contrast, a silver nanoparticle sheet (Acticoat) was covered around the sutured anastomotic line in the AgNPs group. Postoperatively, abdominal ultrasound imaging and the Bristol Rabbit Pain Score (BRPS) were measured on days 7, 15, and 30. Eight rabbits from each group were euthanized at each time point to assess macroscopic findings, bursting pressure tests, tensile strength tests, histopathological examinations, and immunohistochemical analyses. Results The AgNPs group demonstrated a significant increase in the cecal lumen diameter wall (p ≤ 0.001), burst pressure measurement (p ≤ 0.02), and tensile strength (p ≤ 0.01). Conversely, the AgNPs group had significantly lower BRPS scores (p ≤ 0.01). In addition, histopathological examinations revealed that AgNPs significantly reduced inflammatory cell infiltration (neutrophils and macrophages) and enhanced collagen deposition. Immunohistochemical analyses revealed a significant increase (p ≤ 0.01) of α-SMA and a reduction of CD31 in the anastomotic tissue of the AgNPs group. Discussion The results of the present study indicate that the utilization of the AgNPs sheet (Acticoat®) effectively enhanced the strength of cecum anastomosis, resulting in a reduction in anastomosis leakages, pain scores, and abdominal adhesions. Additionally, the bursting pressure values in the rabbit model were significantly increased.